2013
DOI: 10.4314/jab.v67i0.95046
|View full text |Cite
|
Sign up to set email alerts
|

A review of somaclonal variation in plantain (<i>Musa</i> spp): mechanisms and applications

Abstract: Micropropagation or tissue culture is an integral component of applied biotechnology, and is routinely used in different laboratories worldwide. Plant tissue has contributed immensely in large-scale production of resistant and pest free plantlets, germplasm exchange and conservation. A common feature of in vitro-regenerated plants is the potential of genetic variation generated during tissue culture called somaclonal variation, which can be passed onto progeny. Objective: This paper reviews the factors respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…However, RAPD generate monomorphic bands with no polymorphism. The low polymorphism % detected by SRAP may possibly due to repeated subculturing up to seven as reported in earlier studies (Nwauzoma &Jaja, 2013 andSafarpour et al, 2017). The rate of genetic variation induced in the current study is seemingly less than previously reported for banana shoot meristem cultures of 0-70% polymorphism (Smith, 1988 andVuylsteke et al, 1991).…”
Section: Resultssupporting
confidence: 42%
“…However, RAPD generate monomorphic bands with no polymorphism. The low polymorphism % detected by SRAP may possibly due to repeated subculturing up to seven as reported in earlier studies (Nwauzoma &Jaja, 2013 andSafarpour et al, 2017). The rate of genetic variation induced in the current study is seemingly less than previously reported for banana shoot meristem cultures of 0-70% polymorphism (Smith, 1988 andVuylsteke et al, 1991).…”
Section: Resultssupporting
confidence: 42%
“…External factors like growth regulators, temperature, light, osmolarity and agitation rate of the culture medium are known to influence the cell cycle in vivo in plants, considerably, which indicates that inadequate control of cell cycle in vitro is one of the causes of somaclonal variation (Karp 1994; Nwauzoma and Jaja 2013). Normal cell cycle controls, which prevent cell division before the completion of DNA replication, are presumed to be disrupted by tissue culture, resulting in chromosomal breakage (Phillips et al 1994).…”
Section: Sources Of Variations Detected In Plant Tissue Culturementioning
confidence: 99%
“…Among factors affecting somaclonal variation, plant genotype is probably the most important determinant of variation (Shen et al 2007; Tican et al 2008; Nwauzoma and Jaja 2013). Earlier, Eeuwens et al (2002) characterized oil palm clones as low/moderate risk and high risk with regard to ‘mantle’ flowering (wherein anther primordia in both male and female flowers turn into fleshy supplementary carpels), on the basis of terminal inflorescence data generated under in vitro conditions.…”
Section: Sources Of Variations Detected In Plant Tissue Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Such variation commonly occur in both in vitro and in vivo propagated Musa and had both positive and negative impact. Sometimes these variations create major obstacle for clonal uniformity (Nwauzoma and Jaja, 2013) but also exploited as source of genetic improvement of vegetatively propagated crops.…”
Section: Introductionmentioning
confidence: 99%